Expressing OsiSAP8, a Zinc-Finger Associated Protein Gene, Mitigates Stress Dynamics in Existing Elite Rice Varieties of the 'Green Revolution' - Krishnan Subramanian Radhesh; Muthuramalingam Pandiyan; Priya Arumugam Mohana; Prasanth Mani Iyer; Gopinath Krishnasamy; Mohan Chakravarthi; Muthusamy Karthikeyan; Balamurugan Krishnaswamy; Gupta Aditya Kumar; Ramesh Manikandan (MDPI, 2025)
Key message: Overexpression of OsiSAP8 driven by Port Ubi2.3 from Porteresia coarctata imparts drought and salinity stress tolerance in transgenic rice. Stress associated proteins (SAPs) possess the zinc-finger domains that are wildly evolving functional and conserved regions/factors in plants to combat abiotic stresses. In this study, the promoter region of OsiSAP8, an intron-less, multiple stress inducible gene, was compared in silico with a strong constitutive promoter, Port Ubi2.3. This resulted in developing rice, resistant to drought and salinity expressing OsiSAP8 promoted by Port Ubi2.3. (Porteresia coarctata), through Agrobacterium-mediated transformation in the popular rice varieties, IR36 and IR64. Southern blot hybridization confirmed the integration of OsiSAP8, and the T0 transgenic lines of IR36 and IR64 were evaluated for their drought and salinity tolerance. The IR36-T1 progenies showed an enhanced tolerance to water withhold stress compared to wild type and IR64-T1 progenies. Physiological parameters, such as the panicle weight, number of panicles, leaf wilting, and TBARS assay, showed the transgenic IR36 to be superior. The transgenic lines performed better with higher 80-95% relative leaf water content when subjected to drought for 14 days. Gene expression analysis of OsiSAP8 in IR36 T1 showed a 1.5-fold upregulation under mannitol stress. However, IR64 T1 showed a two-fold upregulation in NaCl stress. An enhanced drought and salinity stress tolerance in the transgenic IR36 cultivar through overexpression of OsiSAP8 was observed as it had a native copy of OsiSAP8. This is perhaps the first study using a novel ubiquitin promoter (Port Ubi2.3) to generate drought and salinity stress-tolerant transgenic rice. Thus, we report the overexpression of a rice gene (OsiSAP8) by a rice promoter (Port Ubi2.3) in rice (IR36) to resist drought and salinity.